nothing that 3 raise to 2=9,formulate a simple procedure for converting base 3 numbers to base 9.use the procedure to solve (2111201102220112)base 3 to base 9.

I'm sure that there's some "pull the ripcord and the whole thing falls into a nice answer" approach, but I would just convert the base 8 to base 10 and make some guesses (e.g., you know it's not base 8) cause the two would be equal. That should give you more than enough to go on.

EDIT: Okay, I'm not going to do your homework for you. There are exactly 18 gazillion (base 10) websites out there that cover this stuff. I'd be willing to bet that going from base 3 to base 9 is similar to going from base 2 to base 8 ;) (and not unlike going from 2 to 16).

Not that I'm going to help, because I'm not, but the origin of number systems has nothing to do with programming languages, so I don't understand your response, Seten.

Here is a way you can solve it : (152)_8 = (1 * 8^2 ) + (5 * 8^1) + (2*8^0) = 64 + 40 + 2 = (106)_10 Similarly : (211)_x = (2 * x^2) + (1 * x^1) + (1 * x^0) = 2x^2 + x + 1 Now we need it to be : 2x^2 + x + 1 = (106)_10 To do that we start inputting values for x, particularly starting from base 3 and up. Ex : base 3 : 2x^2 + x + 1 becomes 2(3)^2 + (3) + 1 = 18 + 3 + 1 = 22 == (106)_10 (FALSE)Ex : base 5 : 2x^2 + x + 1 becomes 2(5)^2 + (5) + 1 = 50 + 5 + 1 = 56 == (106)_10 (FALSE)Ex : base 7 : 2x^2 + x + 1 becomes 2(7)^2 + (7) + 1 = 98 + 7 + 1 = 106 == (106)_10( TRUE) From there we see that its base 7, since it matches the other answer.

And keep in mind that from firstPerson's educated guessing you can derive a formula to always get the correct result without any guessing whatsoever, but again, I hope nobody wastes their time doing that for you.

Not that I'm going to help, because I'm not, but the origin of number systems has nothing to do with programming languages, so I don't understand your response, Seten.

Sorry,
Now I realized, that the 'if' is not part of the expression.